2015
DOI: 10.3389/fonc.2015.00113
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Characteristics of Young Non-Small Cell Lung Cancer Patients in the United States

Abstract: BackgroundAlthough the median age at diagnosis of non-small cell lung cancer (NSCLC) is 70 years, a subset of patients with NSCLC present at a younger age (<40 years). Little is known about the time-trends in incidence of NSCLC in the young, their characteristics and outcomes.MethodsThe surveillance, epidemiology, and end results database was used to extract NSCLC cases from 1978 to 2010. Yearly incidence rates in various age groups, race, site of disease, histology, treatment patterns, and outcomes were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
66
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 38 publications
(32 reference statements)
10
66
1
Order By: Relevance
“…3,4 Although previous studies have investigated NSCLC outcomes, they tended to evaluate subgroups of patients, such as patients from specific regions, of specific ages, or who underwent surgery, or to focus on the effects of specific histological type or stage on survival. [5][6][7][8][9][10][11] In addition, accumulating evidence of significant racial and socioeconomic status (SES) disparities in the U.S. health care system has been attracting increased attention. We used period analysis in this study to demonstrate the shift in survival time in each decade between 1983 and 2012 and to determine the impacts of race, sex, age, and SES on the survival rates in patients with NSCLC, using data from the SEER program of the National Cancer Institute.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Although previous studies have investigated NSCLC outcomes, they tended to evaluate subgroups of patients, such as patients from specific regions, of specific ages, or who underwent surgery, or to focus on the effects of specific histological type or stage on survival. [5][6][7][8][9][10][11] In addition, accumulating evidence of significant racial and socioeconomic status (SES) disparities in the U.S. health care system has been attracting increased attention. We used period analysis in this study to demonstrate the shift in survival time in each decade between 1983 and 2012 and to determine the impacts of race, sex, age, and SES on the survival rates in patients with NSCLC, using data from the SEER program of the National Cancer Institute.…”
Section: Introductionmentioning
confidence: 99%
“…Non-small cell lung cancer (NSCLC) accounts for >85% of all cases of lung cancer. NSCLC is primarily treated by surgery (2), however, patients diagnosed in the advanced stages of the disease often may not qualify for surgery. In such cases, immunotherapy may be a promising therapeutic strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies concluded that young patients had a longer survival [10,12,13,[15][16][17][18], although the authors sometimes acknowledged that they received more aggressive treatment, others found a shorter survival [19], and many studies did not find any survival difference between young and older patients [9,14,[21][22][23][24]. However, these results cannot be compared because the cut-off used to define young patients varies from 40 to 50 years, and the populations included in these studies are heterogeneous, sometimes limited to non-small cell lung cancer (NSCLC) or adenocarcinoma or restricted to patients who underwent surgery.…”
Section: Introductionmentioning
confidence: 99%